TRANSLATION CHALLENGES IN SCREENWRITING: NETFLIX & YOUTUBE DIALOGUE TRANSLATION - Subramaniam, Kalaimathi; Kanapathy, Kaaminy (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study investigates the key challenges involved in translating screen dialogue for global streaming platforms, particularly Netflix and YouTube. As audiovisual content increasingly crosses linguistic and cultural boundaries, accurate translation becomes essential for maintaining meaning, emotion and viewer engagement. However, this process is constrained by linguistic ambiguity, idiomatic expressions, cultural references, time and space limitations, and the growing reliance on machine translation. Through selected examples from English–Tamil translations, the study demonstrates how meaning is often distorted due to literal translation, cultural mismatch and mechanical errors. It further examines the differences between professionally produced subtitles on Netflix and user- or machine-generated captions on YouTube, highlighting issues of consistency and quality control. The findings suggest that effective screen translation requires cultural competence, contextual understanding, and human–machine collaboration. This paper concludes that improving subtitle quality is not merely a technical concern but a linguistic and cultural responsibility that directly impacts audience comprehension and the authenticity of global media content.